Determinants of COVID-19 prevention equipment readiness in families during pandemic in Indonesia - Pawitra, Aditya Sukma; Khuliyah Candraning Diyanah; Mohd. Talib Latif; Zainul Amiruddin Zakaria; Al Firdausi, Salsabila (Penerbit Universiti Kebangsaan Malaysia, 2022)
Indonesia was the country with the second-highest case of COVID-19 in the South East Asia Region (SEAR) of the World Health Organization (WHO) data until August 1, 2021. As an infectious disease, the high level of COVID-19 rate transmission requires everyone always to prepare a prevention tools kit to minimize the risk of coronavirus exposure. This study aimed to analyze the determinant factors of readiness of the COVID-19 prevention tools kit. This study used a cross-sectional design with a mix-method technique because data collection and analysis combine quantitative and qualitative approaches in several phases of the research process. Data collected from 18 representative provinces in Indonesia with a total of respondents involved were 2,196 people. The Binary Logistic Regression tests were used to analyze the variable correlation. The multivariable analytic showed that the determinant factors with a significant correlation which affected the readiness of COVID-19 prevention tools kit in each family during pandemic in Indonesia were age 37-46 years old (p=0.000; odds ratio=8.039), female gender (p=0.000; odds ratio=8.653), self-employed jobs (p=0.028; odds ratio=2.239), income > 5 million per month (p=0.000; odds ratio=7.267), good knowledge (p=0.000; odds ratio=3.311), and good perception (p=0.001; odds ratio=2.015). The supply of tools and medicines to prevent COVID-19 is indispensable during the pandemic to protect against COVID-19 infection. Masks and hand sanitizers become the main kits most individuals have, especially when doing outside home activities. At the same time, the oximeter becomes the least kit in the family. This preparation also teaches citizens to practice a healthy lifestyle. Cross-sector coordination is needed to improve public awareness of COVID-19 prevention equipment.